A Case Report on Myoepithelial carcinoma of breast treated with Multi modality approach - Dr. Matangi; Dr. Kashyap M; Dr. Geeta SN; Dr. S. Narayanan (International Journal of Medical Science and Clinical Research Studies, 2024)
Background: Myoepithelial carcinomas are extremely rare in occurrence with limited number of published articles of malignant myoepitheliomas arising from the breast Case Report: A 42 year old female patient presented at an outside center with complaints of pain in left breast , sonomammogram was suggestive of lobulated inhomogenous hypoechoic tumor with smooth margins and multiple cystic areas within the tumor involving all quadrants of breast with size of 13.31X8.83X12.04cm.Patient received Adjuvant Radiation of 50Gy in 25 fractions to the chest wall and axilla and followed by Adjuvant Chemotherapy with four cycles of Adriamycin and Cyclophosphamide and four cycles of paclitaxel. Conclusion: Early detection and multimodality approach is usually required for the management of Myoepithelial carcinoma of Breast.